Pathways for rural-based universities transformation into entrepreneurial institutions in South - Kativhu, Simbarashe; Netshandama, Vhonani (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
For close to three decades, the entrepreneurial university has been growing at a slow pace in the developed countries but recently the developing countries have raised interest in adopting the concept. However, most universities in developing nations including in South Africa have largely relied on Eurocentric frameworks to guide them in adopting the entrepreneurial thrust into their strategic plans. This generic approach can be detrimental given the economic disparities, digital divide, and local needs between developed and developing universities. Therefore, drawing lessons from literature and case studies, the current paper seeks to contextualise the adoption of entrepreneurial universities in rural-based universities of South Africa. The paper seeks to demonstrate how a rural-based university can transform and embrace entrepreneurial drivers and components. A systematic review approach was followed to search and synthesise literature from Web of Science and Scopus databases. The bibliometrics program was utilised to statistically quantify scholarly material and the distribution of science on entrepreneurial knowledge while the Atlas ti 9 software platform was used to synthesise literature. Results showed that drivers of entrepreneurial universities are influenced by local socio-economic conditions and thus, rural-based universities need to conduct baseline studies that inform their implementation strategies. Suggested conceptual pathways to entrepreneurial transformation include curriculum rethink, inculcation of the entrepreneurial culture, enhancement of partnerships with local businesses and improvement of internationalisation